The impact of organo‐montmorillonite on rheology and crystalline structure of uncured and cured acrylonitrile‐butadiene rubber/poly(ethylene‐co‐vinyl acetate) nanocomposites - Razavi‐Nouri, Mohammad; Sabet, Alireza; Mohebbi, Maryam (Polymer composites, 2021)
The aim of this study was to evaluate the influence of organo‐montmorillonite (OMMT) content on rheology, crystalline structure, and also hardness and tensile properties of uncured and lightly cured acrylonitrile‐butadiene rubber (NBR)/poly(ethylene‐co‐vinyl acetate) (EVA)/OMMT nanocomposites. The nanocomposites containing 0 to 7 wt% OMMT was prepared and then cured with 0.3 wt% dicumyl peroxide. The low‐angle X‐ray diffraction results revealed that curing clearly improved the degree of exfoliation in the materials having high OMMT content. It was found from the hardness and tensile tests that the values of hardness, tensile strength, modulus, and energy at break were higher for the cured nanocomposites than those of the uncured materials in the range of OMMT examined. The results obtained from the Casson plot revealed that the nanofiller played a more effective role in increasing the yield stress of the uncured materials than that of the cured counterparts at a constant OMMT content. The characteristic relaxation time was also progressively increased with OMMT content for the uncured materials; however, the value was higher for the cured materials and it was much less sensitive to the nanofiller content. The I110/I200 peak intensity ratio of EVA calculated from the wide‐angle X‐ray diffraction patterns decreased with increasing in OMMT content for the uncured and cured materials; however, the value was always higher for the cured counterparts.